Interaksi Hubungan antara Foreign Direct Investment dan Pertumbuhan Ekonomi - IFA, KHOIRUL; Indrianasari, Neny Tri; Nawangsih, Nawangsih (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2019)
In ASEAN 5 countries namely Indonesia, Vietnam, Thailand, the Philippines and Malaysia have almost the same culture, in terms of social and economic aspects, the 5 countries have links between one country and another, so it is possible that the flow of foreign investment has a close relationship with economic growth. This study aims to determine the relationship between Foreign Direct Investment (FDI) and Economic Growth in ASEAN 5 Periods 1986-2017. This research is a two-way relationship research between the independent variable and the dependent variable that are reciprocal. The type of data used is the 1986-2017 time series data. Sources of data obtained from the World Bank. Data analysis technique uses Granger Causality analysis to see the 2-way relationship, and VAR (Vector Auto Regression) analysis by looking at the implus response factor for non-stationary data using VECM (Vector Error Correction Model) analysis. The results of the study state that based on the Granger Causality test there is no relationship between FDI and GDP and vice versa between GDP and FDI. Based on the VECM test there is a relationship between FDI and GDP.